Medicinal Use of Different Cannabis Strains: Results from a Large Prospective Survey in Germany - Szejko, Natalia; Becher, Eva; Heimann, Florian; Grotenhermen, Franjo; Müller-Vahl, Kirsten R. (Pharmacopsychiatry, 2024)
Background Up to now, it is unclear whether different medicinal cannabis (MC) strains are differently efficacious across different medical conditions. In this study, the effectiveness of different MC strains was compared depending on the disease to be treated.Methods This was an online survey conducted in Germany between June 2020 and August 2020. Patients were allowed to participate only if they received a cannabis-based treatment from pharmacies in the form of cannabis flowers prescribed by a physician.Results The survey was completed by n=1,028 participants. Most participants (58%) have used MC for more than 1 year, on average, 5.9 different strains. Bedrocan (pure tetrahydrocannabinol to pure cannabidiol [THC:CBD]=22:<1) was the most frequently prescribed strain, followed by Bakerstreet (THC:CBD=19:<1) and Pedanios 22/1 (THC:CBD=22:1). The most frequent conditions MC was prescribed for were different pain disorders, psychiatric and neurological diseases, and gastrointestinal symptoms. Overall, the mean patient-reported effectiveness was 80.1% (range, 0–100%). A regression model revealed no association between the patient-reported effectiveness and the variety. Furthermore, no influence of the disease on the choice of the MC strain was detected. On average, 2.1 side effects were reported (most commonly dry mouth (19.5%), increased appetite (17.1%), and tiredness (13.0%)). However, 29% of participants did not report any side effects. Only 398 participants (38.7%) indicated that costs for MC were covered by their health insurance.Conclusions Patients self-reported very good efficacy and tolerability of MC. There was no evidence suggesting that specific MC strains are superior depending on the disease to be treated.
Keywords: medicinal cannabis; tetrahydrocannabinol; cannabidiol; patients’ experience; side effects